Genetic characterization and regional distribution of lymnaeid snails in northern Patagonia, Argentina - Soler, Paula (2023)
Lymnaeid snails serve as intermediate hosts for Fasciola hepatica (Linnaeus, 1758), the etiological agent of fasciolosis, which is a widespread livestock disease in Argentina. Determining their geographic distribution and identifying the snail species involved in the transmission of fasciolosis can provide crucial information for designing strategic control programs. In this context, this work aimed at genetically characterizing the species of lymnaeid snails collected in different water bodies of northern Patagonia, Argentina. To this end, 689 snails were collected in 12 sites in the provinces of Neuquén, Río Negro and Chubut, in areas where fasciolosis is endemic. According to the morphological characteristics of their valves, they were identified as Galba spp. Twenty-three of these specimens were further identified using the nuclear sequences of the internal transcribed spacers ITS-1 and ITS-2 and 18S rRNA. The results confirmed the identity of all the analyzed snails as Galba viatrix and provided evidence that studying the variable region V2 of the 18S rRNA gene is not enough to differentiate closely related species, as observed in lymnaeid snails. Both the fact that G. viatrix was the only species identified in the endemic area surveyed and previous evidence of the high prevalence of F. hepatica infestation in grazing animals in the region suggest that this species is the main intermediate host of F. hepatica. The correct identification of lymnaeid snail species has great importance to determine risk zones and develop appropriate control measures to reduce transmission, according to the different ecological characteristics of each species.